Use of commercial enzyme immunoassays and immunomagnetic separation systems for detecting Escherichia coli O157 in bovine fecal samples. - Chapman, P A (1997)
A commercial enzyme immunoassay (EIA) (E. coli O157 Visual Immunoassay; Tecra Diagnostics) performed on enrichment cultures in modified Escherichia coli broth (mECn) was compared with immunomagnetic separation (IMS) (Dynabeads anti-E. coli O157; Dynal) performed on enrichment cultures in modified buffered peptone water (BPW-VCC) for the detection of E. coli O157 in bovine fecal samples. Tests on fecal suspensions inoculated with each of 12 different strains of E. coli O157 showed that both the EIA and IMS methods were 10- to 100-fold more sensitive than direct culture or enrichment subculture methods for detection of the organism. EIA and IMS were then compared for detection of E. coli O157 in bovine rectal swabs. For confirmation of positive EIA tests, a commercial system (Immunocapture System [ICS]; Tecra Diagnostics) was compared with IMS; both were performed on mECn enrichment cultures. Of 200 rectal swabs examined, 17 gave positive results in the EIA which were confirmed by both confirmation systems, 2 gave positive results in the EIA which were confirmed by IMS but not by ICS, and 1 gave a positive result in the EIA which was confirmed by ICS but not by IMS. Of these 20, 15 were also positive by the BPW-VCC-IMS culture system; a further 3 samples were positive by this culture system but gave a negative result in the EIA. Eight samples were negative by the BPW-VCC-IMS culture system but gave a positive result in the EIA which could not be confirmed by either confirmation system. Further examination of the eight unconfirmed EIA-positive samples yielded sorbitol-fermenting E. coli O157 from three samples. Of the remaining five cultures, four were positive in an EIA for verocytotoxins (VT) and two were positive in a cell culture assay for VT1. The remaining 170 samples were negative by both EIA and BPW-VCC-IMS. The Tecra EIA and IMS are both technically simple and sensitive methods for detecting E. coli O157 in bovine fecal samples. There was no statistically significant difference between the numbers of positives detected by the different assays (P = 0.29).